2000
DOI: 10.1051/forest:2000112
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of an excess Al and a deficiency in Ca and Mg for stomatal functioning and net carbon assimilation of beech leaves

Abstract: -Stomatal function and photosynthesis were investigated in beech seedlings submitted to excess Al, or/and to a deficiency in Ca and Mg. Excess Al in the nutrient solution promoted a decrease of Ca and Mg leaf contents, while K was increased. Stomatal responses to darkness, ABA and ambient CO 2 remained normal. In contrast, steady-state stomatal conductance in light was significantly smaller and correlated to a lower accumulation of K in the guard cells. Similar stomatal responses were observed for Ca-Mg defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The decrease in root surface area due to high Al concentration can be similarly explained by deficiency of calcium and magnesium as reported by Ridolfi and Garrec (2000); Godbold et al (1988) and Tan and Keltjens (1995). Arp and Strucel (1989) reported that water uptake of 1-yearold black spruce was reduced by exposure to high concentration of Al.…”
Section: Inhibition Of Root Growthsupporting
confidence: 50%
See 1 more Smart Citation
“…The decrease in root surface area due to high Al concentration can be similarly explained by deficiency of calcium and magnesium as reported by Ridolfi and Garrec (2000); Godbold et al (1988) and Tan and Keltjens (1995). Arp and Strucel (1989) reported that water uptake of 1-yearold black spruce was reduced by exposure to high concentration of Al.…”
Section: Inhibition Of Root Growthsupporting
confidence: 50%
“…It is believed that reduced root length results in decreased nutrient uptake and multiple nutrient deficiencies. Ridolfi and Garrec (2000) reported that the concentration of calcium and magnesium in beech leaf was reduced by Tan and Keljens (1995). Furthermore, Ryan et al (1993) reported that roots of an aluminum-sensitive corn cultivar BR 201F was inhibited after 30 min of exposure to aluminum.…”
Section: Discussionmentioning
confidence: 99%
“…Both Mg deficiency and Mg excess have detrimental effects on plant photosynthesis (Shabala and Hariadi, 2005). There are several reports that photosynthesis rate is significantly declined in leaves of Mg deficient plants (Fischer, 1997;Sun and Payn, 1999;Ridolfi and Garrec, 2000;Hermans and Verbruggen, 2005). Due to temperature stress the reactive oxygen species (ROS) are produced continuously as byproducts of different metabolic pathways which are located in different cellular compartments such as chloroplast, mitochondria and peroxisomes (Rio et al, 2006;Navrot et al, 2007).…”
Section: Calciummentioning
confidence: 99%
“…This has been also reported in other plant species, such as citrus (Chen et al, 2005a;Jiang et al, 2008Jiang et al, , 2009aJiang et al, and 2009b, soy beans (Milivojevi et al, 2000;Ying and Liu, 2005), sorghum (Peixoto et al, 2002), rice (Oryza sativa) (Kuo and Kao, 2003); wheat (Okhi, 1986), beech (Ridolfi and Garrec, 2000) and barely (Hordeum vulgare) (Abdalla, 2008). Although it should be noted that a decrease in chlorophyll content to a greater extent in response to aluminium was probably not the primary factor to limit photosynthetic ability of the plants (Jiang et al, 2008(Jiang et al, , 2009a(Jiang et al, and 2009bLi-Song et al, 2010).…”
Section: Total Chlorophyll (A + B) Chlorophyll a And B And Chlorophymentioning
confidence: 89%